The Effects of Helicobacter pylori Infection on Microbiota Associated With Gastric Mucosa and Immune Factors in Children - Zheng, Wei; Miao, Jing; Luo, Lingling; Long, Gao; Chen, Bo; Shu, Xiaoli; Gu, Weizhong; Peng, Kerong; Li, Fubang; Zhao, Hong; Botchway, Benson O. A.; Fang, Marong; et al. (Frontiers in Immunology, 2021)
Background: Helicobacter pylori infection is the main cause of chronic gastritis in children. Little is known about the effect of Helicobacter pylori on microbiota and immunity. This study was aimed at characterizing stomach microbiota and immune-regulatory properties of children with Helicobacter pylori colonization. Methods: We studied 122 children who had undergone gastric endoscopy due to gastrointestinal symptoms, 57 were diagnosed with Helicobacter pylori infection. Endoscopic mucosal biopsy samples were obtained for DNA and RNA extraction. Microbiomes were analyzed by 16S rRNA profiling, with the differentially expressed genes analyzed using RNA sequencing. The RNA-sequencing results of selected genes were validated by qRT-PCR. Results: Bacterial diversity of Helicobacter pylori-positive gastric specimens were lower than those of negative, and both groups were clearly separated according to beta diversity. Helicobacter pylori-positive group significantly reduced proportions of six phyla and eight genera; only Helicobacter taxa were more abundant in Helicobacter pylori-negative group. Gastric tissues RNA sequencing showed increased expression of multiple immune response genes in Helicobacter pylori -infection. Helicobacter pylori -infected children with restructured gastric microbiota had higher levels of FOXP3, IL-10, TGF-β1 and IL-17A expressions, which were consistent with increased CD4+T cell and macrophagocyte, compared with non-infected children. Conclusions: Presence of Helicobacter pylori significantly influences gastric microbiota and results in lower abundance of multiple taxonomic levels in children. Meanwhile, it affects gastric immune environment and promotes the occurrence of gastritis.